The Relationship Between Smoking Habits and Recurrence of Coronary Heart Disease (CHD) at Santosa Hospital Bandung Central - IRAWAN, ERNA; Iklima, nurul; tania, mery; Maryani, Elis; Saputra, anggi (Sahabat Publikasi Kuu, 2024)
Abstract Background: Coronary heart disease (CHD) is caused by the narrowing of coronary arteries due to atherosclerosis or the buildup of fatty plaques on the arterial walls. CHD is the leading cause of death worldwide for non-communicable diseases. Purpose: This study aims to determine the relationship between smoking habits and the recurrence of coronary heart disease (CHD) at Santosa Hospital Bandung Central in 2023. Methods: This study is a correlational analysis with a cross-sectional approach. The population consisted of coronary heart disease patients who smoked and attended the cardiac clinic, totaling 95 respondents. The sample was obtained using total sampling, resulting in 95 respondents. This study used univariate and bivariate analysis. Univariate analysis was done using percentages. Bivariate analysis was used to determine the correlation between smoking habits and CHD recurrence using Spearman's rank correlation. Results: The study results showed that smoking habits in CHD patients indicated that almost half (45.7%) or 43 respondents were moderate smokers. Most of the respondents (62.10%) or 59 patients did not experience recurrence. The P-value was 0.001 < 0.05, with an r-value of 0.7007, indicating a significant relationship between smoking habits and CHD recurrence at Santosa Hospital Bandung Central. Conclusions: There is a significant relationship between smoking habits and the recurrence of coronary heart disease (CHD). The results of this study can be a source of input and evaluation for hospitals to improve services to prevent smoking, especially among the youth, as well as smoking cessation programs, which are essential to reducing the prevalence and recurrence of coronary heart disease (CHD).